Yttria-stabilised zirconia and lanthanum cerate granules with YSZ whiskers prepared by spray drying for thermal barrier coatings - Milan Parchovianský; Monika Michálková; Ivana Parchovianská; Beáta Pecušová; Dušan Galusek; Amirhossein Pakseresht (Open Ceramics)
The aim of this study was to explore the effect of different solid phases and varied amounts of polyvinyl alcohol (PVA) on granule size of plasma-sprayable yttria-stabilised zirconia (YSZ) with YSZ whiskers (YSZ/W) and lanthanum cerate (La2Ce2O7, LC) with YSZ whiskers (LC/W) as composite powders. The initial phase of this study involved the preparation and optimization of a YSZ suspension using varying solid loadings of YSZ powder (ranging from 30 to 75 wt%) and PVA serving as both a binder and dispersant. The suspension was subjected to rigorous optimization procedures to meet the required standards. The suspensions were spray dried, and the resulting granulates were examined using SEM to determine their shape and size. The particle size of YSZ granules increased with increasing solid loading of YSZ in the suspension. The optimum amount of dispersant was found to be 1 wt% related to the weight of solid, while the solid loading was 75 wt% of YSZ. In some cases, excessive YSZ solid loading and dispersant impaired the formation of spherical granules. Composite YSZ/W and LC/W granules were also prepared with spherical, lemon, or irregular shapes, with the whiskers embedded in the YSZ or LC powder.